If there is one prayer that you should pray/sing every day and every hour, it is the
LORD's prayer (Our FATHER in Heaven prayer)
- Samuel Dominic Chukwuemeka
It is the most powerful prayer.
A pure heart, a clean mind, and a clear conscience is necessary for it.
For in GOD we live, and move, and have our being.
- Acts 17:28
The Joy of a Teacher is the Success of his Students.
- Samuel Chukwuemeka
Verify your answers with these Calculators as applicable.
For ACT Students
The ACT is a timed exam...$60$ questions for $60$ minutes
This implies that you have to solve each question in one minute.
Some questions will typically take less than a minute a solve.
Some questions will typically take more than a minute to solve.
The goal is to maximize your time. You use the time saved on those questions you
solved in less than a minute, to solve the questions that will take more than a minute.
So, you should try to solve each question correctly and timely.
So, it is not just solving a question correctly, but solving it correctly on time.
Please ensure you attempt all ACT questions.
There is no negative penalty for a wrong answer.
For SAT Students
Any question labeled SAT-C is a question that allows a calculator.
Any question labeled SAT-NC is a question that does not allow a calculator.
For JAMB and CMAT Students
Calculators are not allowed. So, the questions are solved in a way that does not require a calculator.
For WASSCE Students
Any question labeled WASCCE is a question for the WASCCE General Mathematics
Any question labeled WASSCE:FM is a question for the WASSCE Further Mathematics/Elective Mathematics
For GCSE Students
All work is shown to satisfy (and actually exceed) the minimum for awarding method marks.
Calculators are allowed for some questions. Calculators are not allowed for some questions.
For NSC Students
For the Questions:
Any space included in a number indicates a comma used to separate digits...separating multiples of three digits from behind.
Any comma included in a number indicates a decimal point.
For the Solutions:
Decimals are used appropriately rather than commas
Commas are used to separate digits appropriately.
Solve the trigonometric equations
Determine the specific solutions of the trigonometric equations in the specified intervals
Check your solutions
Write the general solution of the trigonometric equations
State the reasons for every step
Show all work
Unless otherwise specified or implied, only the exact values are allowed.
$
\underline{LHS} \\[3ex]
\theta = 210^\circ \\[3ex] \\[3ex]
4\sin \theta + 5 \\[3ex]
= 4 * \sin210 + 5 \\[5ex]
= 4 * -\dfrac{1}{2} + 5 \\[5ex]
= -2 + 5 \\[3ex]
= 3 \\[3ex]
$
$ \theta = 330^\circ \\[3ex] 4\sin \theta + 5 \\[3ex] = 4 * \sin 330 + 5 \\[3ex] = 4 * -\dfrac{1}{2} + 5 \\[5ex] = -2 + 5 \\[3ex] = 3 $ |
$ \underline{RHS} \\[3ex] 3 $ |
$
\underline{LHS} \\[3ex]
\beta = \dfrac{\pi}{3} \\[5ex]
2\sin\beta - \sqrt{3} \\[3ex]
= 2 * \sin\dfrac{\pi}{3} - \sqrt{3} \\[5ex]
= 2 * \dfrac{\sqrt{3}}{2} - \sqrt{3} \\[5ex]
= \sqrt{3} - \sqrt{3} \\[3ex]
= 0 \\[3ex]
$
$ \beta = \dfrac{2\pi}{3} \\[5ex] 2\sin\beta - \sqrt{3} \\[3ex] = 2 * \sin\dfrac{2\pi}{3} - \sqrt{3} \\[5ex] = 2 * \dfrac{\sqrt{3}}{2} - \sqrt{3} \\[5ex] = \sqrt{3} - \sqrt{3} \\[3ex] = 0 $ |
$ \underline{RHS} \\[3ex] 0 $ |
$
\underline{LHS} \\[3ex]
\tan \theta \\[3ex]
\theta = \dfrac{3\pi}{4} \\[5ex]
\tan \left(\dfrac{3\pi}{4}\right) = -1 \\[5ex]
$
$ \theta = \dfrac{7\pi}{4} \\[5ex] \tan \left(\dfrac{7\pi}{4}\right) = -1 $ |
$ \underline{RHS} \\[3ex] -1 $ |
$ \underline{LHS} \\[3ex] 2\sin^2x^\circ - 1 \\[3ex] x = 45^\circ \\[3ex] 2\sin^2(45) - 1 \\[3ex] 2 * (\sin 45)^2 - 1 \\[3ex] \sin 45 = \dfrac{\sqrt{2}}{2} \\[5ex] (\sin 45)^2 = \left(\dfrac{\sqrt{2}}{2}\right)^2 \\[5ex] (\sin 45)^2 = \dfrac{\sqrt{2}^2}{2^2} \\[5ex] (\sin 45)^2 = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex] = 2 * \dfrac{1}{2} - 1 \\[5ex] = 1 - 1 \\[3ex] = 0 $ | $ \underline{RHS} \\[3ex] 0 $ |
$
\underline{LHS} \\[3ex]
\tan \theta \\[3ex]
\theta = 135^\circ \\[3ex]
\tan 135 = -1 \\[3ex]
$
$ \theta = 315^\circ \\[3ex] \tan 315 = -1 $ |
$ \underline{RHS} \\[3ex] -1 $ |
$
\underline{LHS} \\[3ex]
\sin\alpha - \cos\alpha \\[3ex]
\alpha = \dfrac{\pi}{4} \\[5ex]
\sin\alpha = \sin\dfrac{\pi}{4} = \dfrac{\sqrt{2}}{2} \\[5ex]
\cos\alpha = \cos\dfrac{\pi}{4} = \dfrac{\sqrt{2}}{2} \\[5ex]
= \dfrac{\sqrt{2}}{2} - \dfrac{\sqrt{2}}{2} \\[5ex]
= 0 \\[5ex]
$
$ \alpha = \dfrac{5\pi}{4} \\[5ex] \sin\alpha = \sin\dfrac{5\pi}{4} = -\dfrac{\sqrt{2}}{2} \\[5ex] \cos\alpha = \cos\dfrac{5\pi}{4} = -\dfrac{\sqrt{2}}{2} \\[5ex] = -\dfrac{\sqrt{2}}{2} - -\dfrac{\sqrt{2}}{2} \\[5ex] = -\dfrac{\sqrt{2}}{2} + \dfrac{\sqrt{2}}{2} \\[5ex] = 0 $ |
$ \underline{RHS} \\[3ex] 0 $ |
$
\underline{LHS} \\[3ex]
\cos\alpha + \sqrt{3}\sin\alpha \\[3ex]
\alpha = 120 \\[5ex]
\cos\alpha = \cos 120 = -\dfrac{1}{2} \\[5ex]
\sin\alpha = \sin 120 = \dfrac{\sqrt{3}}{2} \\[5ex]
\sqrt{3}\sin\alpha = \sqrt{3} * \dfrac{\sqrt{3}}{2} = \dfrac{3}{2} \\[5ex]
= -\dfrac{1}{2} + \dfrac{3}{2} \\[5ex]
= -\dfrac{1}{2} + \dfrac{3}{2} \\[5ex]
= \dfrac{-1 + 3}{2} \\[5ex]
= -\dfrac{2}{2} \\[5ex]
= 1 \\[3ex]
YES \\[3ex]
$
$ \alpha = 240 \\[5ex] \cos\alpha = \cos 240 = -\dfrac{1}{2} \\[5ex] \sin\alpha = \sin 240 = -\dfrac{\sqrt{3}}{2} \\[5ex] \sqrt{3}\sin\alpha = \sqrt{3} * -\dfrac{\sqrt{3}}{2} = -\dfrac{3}{2} \\[5ex] = -\dfrac{1}{2} + - \dfrac{3}{2} \\[5ex] = -\dfrac{1}{2} - \dfrac{3}{2} \\[5ex] = \dfrac{-1 - 3}{2} \\[5ex] = -\dfrac{4}{2} \\[5ex] = -2 \\[3ex] Extraneous\:\ root \\[3ex] NO \\[3ex] $ $ \alpha = 0 \\[3ex] \cos\alpha = \cos 0 = 1 \\[3ex] \sin\alpha = \sin 0 = 0 \\[3ex] \sqrt{3}\sin\alpha = \sqrt{3} * 0 = 0\\[3ex] = 1 + 0 \\[5ex] = 1 \\[3ex] YES \\[3ex] $ $ \alpha = 360 \\[3ex] \cos\alpha = \cos 360 = 1 \\[3ex] \sin\alpha = \sin 360 = 0 \\[3ex] \sqrt{3}\sin\alpha = \sqrt{3} * 0 = 0\\[3ex] = 1 + 0 \\[5ex] = 1 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 1 $ |
$
\underline{LHS} \\[3ex]
6\cos^2\theta \\[3ex]
\theta = \dfrac{\pi}{4} \\[5ex]
\cos\theta = \cos\dfrac{\pi}{4} = \dfrac{\sqrt{2}}{2} \\[5ex]
\cos^2\theta = \left(\dfrac{\sqrt{2}}{2}\right)^2 = \dfrac{(\sqrt{2})^2}{2^2} = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex]
= 6 * \dfrac{1}{2} \\[5ex]
= 3 \\[3ex]
$
$ \theta = \dfrac{3\pi}{4} \\[5ex] \cos\theta = \cos\dfrac{3\pi}{4} = -\dfrac{\sqrt{2}}{2} \\[5ex] \cos^2\theta = \left(-\dfrac{\sqrt{2}}{2}\right)^2 = \dfrac{(-\sqrt{2})^2}{2^2} = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex] = 6 * \dfrac{1}{2} \\[5ex] = 3 \\[3ex] $ $ \theta = \dfrac{5\pi}{4} \\[5ex] \cos\theta = \cos\dfrac{5\pi}{4} = \dfrac{\sqrt{2}}{2} \\[5ex] \cos^2\theta = \left(\dfrac{\sqrt{2}}{2}\right)^2 = \dfrac{(\sqrt{2})^2}{2^2} = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex] = 6 * \dfrac{1}{2} \\[5ex] = 3 \\[3ex] $ $ \theta = \dfrac{7\pi}{4} \\[5ex] \cos\theta = \cos\dfrac{7\pi}{4} = -\dfrac{\sqrt{2}}{2} \\[5ex] \cos^2\theta = \left(-\dfrac{\sqrt{2}}{2}\right)^2 = \dfrac{(-\sqrt{2})^2}{2^2} = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex] = 6 * \dfrac{1}{2} \\[5ex] = 3 $ |
$ \underline{RHS} \\[3ex] 3 $ |
$
\underline{LHS} \\[3ex]
\cos\alpha - \sqrt{3}\sin\alpha \\[3ex]
\alpha = 120 \\[5ex]
\cos\alpha = \cos 120 = -\dfrac{1}{2} \\[5ex]
\sin\alpha = \sin 120 = \dfrac{\sqrt{3}}{2} \\[5ex]
\sqrt{3}\sin\alpha = \sqrt{3} * \dfrac{\sqrt{3}}{2} = \dfrac{3}{2} \\[5ex]
= -\dfrac{1}{2} - \dfrac{3}{2} \\[5ex]
= -\dfrac{1}{2} - \dfrac{3}{2} \\[5ex]
= \dfrac{-1 - 3}{2} \\[5ex]
= -\dfrac{4}{2} \\[5ex]
= -2 \\[3ex]
Extraneous\:\ root \\[3ex]
NO \\[3ex]
$
$ \alpha = 240 \\[5ex] \cos\alpha = \cos 240 = -\dfrac{1}{2} \\[5ex] \sin\alpha = \sin 240 = -\dfrac{\sqrt{3}}{2} \\[5ex] \sqrt{3}\sin\alpha = \sqrt{3} * -\dfrac{\sqrt{3}}{2} = -\dfrac{3}{2} \\[5ex] = -\dfrac{1}{2} - - \dfrac{3}{2} \\[5ex] = -\dfrac{1}{2} + \dfrac{3}{2} \\[5ex] = \dfrac{-1 + 3}{2} \\[5ex] = -\dfrac{2}{2} \\[5ex] = 1 \\[3ex] YES \\[3ex] $ $ \alpha = 0 \\[3ex] \cos\alpha = \cos 0 = 1 \\[3ex] \sin\alpha = \sin 0 = 0 \\[3ex] \sqrt{3}\sin\alpha = \sqrt{3} * 0 = 0\\[3ex] = 1 - 0 \\[5ex] = 1 \\[3ex] YES \\[3ex] $ $ \alpha = 360 \\[3ex] \cos\alpha = \cos 360 = 1 \\[3ex] \sin\alpha = \sin 360 = 0 \\[3ex] \sqrt{3}\sin\alpha = \sqrt{3} * 0 = 0\\[3ex] = 1 - 0 \\[5ex] = 1 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 1 $ |
$
\underline{LHS} \\[3ex]
2\cos^2\theta + 3\cos\theta \\[3ex]
\theta = 180 \\[3ex]
\cos\theta = \cos 180 = -1 \\[3ex]
\cos^2\theta = (\cos 180)^2 = (-1)^2 = 1 \\[3ex]
= 2(1) + 3(-1) \\[3ex]
= 2 - 3 \\[3ex]
= -1 \\[3ex]
YES \\[3ex]
$
$ \theta = 120 \\[3ex] \cos\theta = \cos 120 = -\dfrac{1}{2} \\[3ex] \cos^2\theta = (\cos 120)^2 = \left(-\dfrac{1}{2}\right)^2 = \dfrac{1}{4} \\[3ex] = 2\left(\dfrac{1}{4}\right) + 3\left(-\dfrac{1}{2}\right) \\[3ex] = \dfrac{1}{2} - \dfrac{3}{2} \\[3ex] = \dfrac{1 - 3}{2} \\[5ex] = -\dfrac{2}{2} \\[5ex] = -1 \\[3ex] YES \\[3ex] $ $ \theta = 240 \\[3ex] \cos\theta = \cos 240 = -\dfrac{1}{2} \\[3ex] \cos^2\theta = (\cos 240)^2 = \left(-\dfrac{1}{2}\right)^2 = \dfrac{1}{4} \\[3ex] = 2\left(\dfrac{1}{4}\right) + 3\left(-\dfrac{1}{2}\right) \\[3ex] = \dfrac{1}{2} - \dfrac{3}{2} \\[3ex] = \dfrac{1 - 3}{2} \\[5ex] = -\dfrac{2}{2} \\[5ex] = -1 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] -1 $ |
$
\underline{LHS} \\[3ex]
\sqrt{2}\sin\theta \\[3ex]
\theta = 0 \\[5ex]
\sin\theta = \sin 0 = 0 \\[3ex]
= \sqrt{2} * 0 \\[5ex]
= 0 \\[3ex]
YES \\[3ex]
$
$ \theta = 180 \\[5ex] \sin\theta = \sin 180 = 0 \\[3ex] = \sqrt{2} * 0 \\[5ex] = 0 \\[3ex] YES \\[3ex] $ $ \theta = 45 \\[5ex] \sin\theta = \sin 45 = \dfrac{\sqrt{2}}{2} \\[5ex] = \sqrt{2} * \dfrac{\sqrt{2}}{2} \\[5ex] = \dfrac{2}{2} \\[5ex] = 1 \\[3ex] YES \\[3ex] $ $ \theta = 135 \\[5ex] \sin\theta = \sin 135 = \dfrac{\sqrt{2}}{2} \\[5ex] = \sqrt{2} * \dfrac{\sqrt{2}}{2} \\[5ex] = \dfrac{2}{2} \\[5ex] = 1 \\[3ex] YES $ |
$
\underline{RHS} \\[3ex]
2\sin^2\theta \\[3ex]
\theta = 0 \\[5ex]
\sin\theta = \sin 0 = 0 \\[3ex]
\sin^2\theta = (\sin\theta)^2 = 0^2 = 0 \\[3ex]
= 2 * 0 \\[3ex]
= 0 \\[3ex]
YES \\[3ex]
$
$ \theta = 180 \\[5ex] \sin\theta = \sin 180 = 0 \\[3ex] \sin^2\theta = (\sin\theta)^2 = 0^2 = 0 \\[3ex] = 2 * 0 \\[3ex] = 0 \\[3ex] YES \\[3ex] $ $ \theta = 45 \\[5ex] \sin\theta = \sin 45 = \dfrac{\sqrt{2}}{2} \\[3ex] \sin^2\theta = (\sin\theta)^2 \\[3ex] \sin^2\theta = \left(\dfrac{\sqrt{2}}{2} \right) \\[5ex] \sin^2\theta = \dfrac{(\sqrt{2})^2}{2^2} \\[5ex] \sin^2\theta = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex] = 2 * \dfrac{1}{2} \\[3ex] = 1 \\[3ex] YES \\[3ex] $ $ \theta = 135 \\[5ex] \sin\theta = \sin 135 = \dfrac{\sqrt{2}}{2} \\[3ex] \sin^2\theta = (\sin\theta)^2 \\[3ex] \sin^2\theta = \left(\dfrac{\sqrt{2}}{2} \right) \\[5ex] \sin^2\theta = \dfrac{(\sqrt{2})^2}{2^2} \\[5ex] \sin^2\theta = \dfrac{2}{4} = \dfrac{1}{2} \\[5ex] = 2 * \dfrac{1}{2} \\[3ex] = 1 \\[3ex] YES $ |
$
\underline{LHS} \\[3ex]
6\cos\beta - 6\sin\beta = 6(\cos\beta - \sin\beta) \\[3ex]
\beta = 105^\circ \\[3ex]
\cos\beta = \cos105 = \dfrac{\sqrt{2} - \sqrt{6}}{4} ... Special\:\: Angles\:\: Kids \\[5ex]
\sin\beta = \sin105 = \dfrac{\sqrt{2} + \sqrt{6}}{4} ... Special\:\: Angles\:\: Kids \\[5ex]
\cos\beta - \sin\beta = \dfrac{\sqrt{2} - \sqrt{6}}{4} - \left(\dfrac{\sqrt{2} + \sqrt{6}}{4}\right) \\[5ex]
\cos\beta - \sin\beta = \dfrac{\sqrt{2} - \sqrt{6} - (\sqrt{2} + \sqrt{6})}{4} \\[5ex]
\cos\beta - \sin\beta = \dfrac{\sqrt{2} - \sqrt{6} - \sqrt{2} - \sqrt{6}}{4} \\[5ex]
\cos\beta - \sin\beta = \dfrac{-2\sqrt{6}}{4} = \dfrac{-\sqrt{6}}{2} \\[5ex]
= 6\left(-\dfrac{\sqrt{6}}{2}\right) \\[5ex]
= 3 * -\sqrt{6} \\[3ex]
= -3\sqrt{6} \\[3ex]
Extraneous\:\: root \\[3ex]
NO \\[3ex]
$
$ \beta = 165^\circ \\[3ex] \cos\beta = \cos165 = \dfrac{-\sqrt{6} - \sqrt{2}}{4} ... Special\:\: Angles\:\: Kids \\[5ex] \sin\beta = \sin165 = \dfrac{\sqrt{6} - \sqrt{2}}{4} ... Special\:\: Angles\:\: Kids \\[5ex] \cos\beta - \sin\beta = \dfrac{-\sqrt{6} - \sqrt{2}}{4} - \left(\dfrac{\sqrt{6} - \sqrt{2}}{4}\right) \\[5ex] \cos\beta - \sin\beta = \dfrac{-\sqrt{6} - \sqrt{2} - (\sqrt{6} - \sqrt{2})}{4} \\[5ex] \cos\beta - \sin\beta = \dfrac{-\sqrt{6} - \sqrt{2} - \sqrt{6} + \sqrt{2}}{4} \\[5ex] \cos\beta - \sin\beta = \dfrac{-2\sqrt{6}}{4} = \dfrac{-\sqrt{6}}{2} \\[5ex] = 6\left(-\dfrac{\sqrt{6}}{2}\right) \\[5ex] = 3 * -\sqrt{6} \\[3ex] = -3\sqrt{6} \\[3ex] Extraneous\:\: root \\[3ex] NO \\[3ex] $ $ \beta = 285^\circ \\[3ex] \cos\beta = \cos285 = \dfrac{\sqrt{6} - \sqrt{2}}{4} ... Special\:\: Angles\:\: Kids \\[5ex] \sin\beta = \sin285 = \dfrac{-\sqrt{2} - \sqrt{6}}{4} ... Special\:\: Angles\:\: Kids \\[5ex] \cos\beta - \sin\beta = \dfrac{\sqrt{6} - \sqrt{2}}{4} - \left(\dfrac{-\sqrt{2} - \sqrt{6}}{4}\right) \\[5ex] \cos\beta - \sin\beta = \dfrac{\sqrt{6} - \sqrt{2} - (-\sqrt{2} - \sqrt{6})}{4} \\[5ex] \cos\beta - \sin\beta = \dfrac{\sqrt{6} - \sqrt{2} + \sqrt{2} + \sqrt{6}}{4} \\[5ex] \cos\beta - \sin\beta = \dfrac{2\sqrt{6}}{4} = \dfrac{\sqrt{6}}{2} \\[5ex] = 6\left(\dfrac{\sqrt{6}}{2}\right) \\[5ex] = 3 * \sqrt{6} \\[3ex] = 3\sqrt{6} \\[3ex] YES \\[3ex] $ $ \beta = 345^\circ \\[3ex] \cos\beta = \cos345 = \dfrac{\sqrt{2} + \sqrt{6}}{4} ... Special\:\: Angles\:\: Kids \\[5ex] \sin\beta = \sin345 = \dfrac{\sqrt{2} - \sqrt{6}}{4} ... Special\:\: Angles\:\: Kids \\[5ex] \cos\beta - \sin\beta = \dfrac{\sqrt{2} + \sqrt{6}}{4} - \left(\dfrac{\sqrt{2} - \sqrt{6}}{4}\right) \\[5ex] \cos\beta - \sin\beta = \dfrac{\sqrt{2} + \sqrt{6} - (\sqrt{2} - \sqrt{6})}{4} \\[5ex] \cos\beta - \sin\beta = \dfrac{\sqrt{2} + \sqrt{6} - \sqrt{2} + \sqrt{6}}{4} \\[5ex] \cos\beta - \sin\beta = \dfrac{2\sqrt{6}}{4} = \dfrac{\sqrt{6}}{2} \\[5ex] = 6\left(\dfrac{\sqrt{6}}{2}\right) \\[5ex] = 3 * \sqrt{6} \\[3ex] = 3\sqrt{6} \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 3\sqrt{6} $ |
$
\underline{LHS} \\[3ex]
\cos\alpha + \sqrt{3}\sin\alpha \\[3ex]
\alpha = 120 \\[5ex]
\cos\alpha = \cos 120 = -\dfrac{1}{2} \\[5ex]
\sin\alpha = \sin 120 = \dfrac{\sqrt{3}}{2} \\[5ex]
\sqrt{3}\sin\alpha = \sqrt{3} * \dfrac{\sqrt{3}}{2} = \dfrac{3}{2} \\[5ex]
= -\dfrac{1}{2} + \dfrac{3}{2} \\[5ex]
= -\dfrac{1}{2} + \dfrac{3}{2} \\[5ex]
= \dfrac{-1 + 3}{2} \\[5ex]
= -\dfrac{2}{2} \\[5ex]
= 1 \\[3ex]
YES \\[3ex]
$
$ \alpha = 240 \\[5ex] \cos\alpha = \cos 240 = -\dfrac{1}{2} \\[5ex] \sin\alpha = \sin 240 = -\dfrac{\sqrt{3}}{2} \\[5ex] \sqrt{3}\sin\alpha = \sqrt{3} * -\dfrac{\sqrt{3}}{2} = -\dfrac{3}{2} \\[5ex] = -\dfrac{1}{2} + - \dfrac{3}{2} \\[5ex] = -\dfrac{1}{2} - \dfrac{3}{2} \\[5ex] = \dfrac{-1 - 3}{2} \\[5ex] = -\dfrac{4}{2} \\[5ex] = -2 \\[3ex] Extraneous\:\: root \\[3ex] NO \\[3ex] $ $ \alpha = 0 \\[3ex] \cos\alpha = \cos 0 = 1 \\[3ex] \sin\alpha = \sin 0 = 0 \\[3ex] \sqrt{3}\sin\alpha = \sqrt{3} * 0 = 0\\[3ex] = 1 + 0 \\[5ex] = 1 \\[3ex] YES \\[3ex] $ $ \alpha = 360 \\[3ex] \cos\alpha = \cos 360 = 1 \\[3ex] \sin\alpha = \sin 360 = 0 \\[3ex] \sqrt{3}\sin\alpha = \sqrt{3} * 0 = 0\\[3ex] = 1 + 0 \\[5ex] = 1 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 1 $ |
$
\underline{LHS} \\[3ex]
\cos(\pi + \theta) + \sin\left(\theta - \dfrac{\pi}{2}\right) \\[5ex]
\pi = 180^\circ \\[3ex]
\dfrac{\pi}{2} = \dfrac{180}{2} = 90^circ \\[5ex]
\theta = 120^\circ \\[3ex]
= \cos(180 + 120) + \sin(120 - 90) \\[3ex]
= \cos 300 + \sin 30 \\[3ex]
= \dfrac{1}{2} + \dfrac{1}{2} ... Unit\:\: Circle\:\: Trig \\[5ex]
= 1 \\[3ex]
YES \\[3ex]
$
$ \theta = 240^\circ \\[3ex] = \cos(180 + 240) + \sin(240 - 90) \\[3ex] = \cos 420 + \sin 150 \\[3ex] coterminal\:\: \angle \:\:of\:\: 420 = 420 - 360 = 60 \\[3ex] = \cos 60 + \sin 150 \\[3ex] = \dfrac{1}{2} + \dfrac{1}{2} ... Unit\:\: Circle\:\: Trig \\[5ex] = 1 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 1 $ |
$
\underline{LHS} \\[3ex]
\cot\beta + \sqrt{3} \\[3ex]
\beta = 120^\circ \\[5ex]
\cot\beta = \cot 120 = -\dfrac{\sqrt{3}}{3} \\[5ex]
= -\dfrac{\sqrt{3}}{3} + \sqrt{3} \\[5ex]
= -\dfrac{\sqrt{3}}{3} + \dfrac{3\sqrt{3}}{3} \\[5ex]
= \dfrac{-\sqrt{3} + 3\sqrt{3}}{3} \\[5ex]
= \dfrac{2\sqrt{3}}{3} \\[3ex]
YES \\[3ex]
$
$ \beta = 300^\circ \\[5ex] \cot\beta = \cot 300 = -\dfrac{\sqrt{3}}{3} \\[5ex] = -\dfrac{\sqrt{3}}{3} + \sqrt{3} \\[5ex] = -\dfrac{\sqrt{3}}{3} + \dfrac{3\sqrt{3}}{3} \\[5ex] = \dfrac{-\sqrt{3} + 3\sqrt{3}}{3} \\[5ex] = \dfrac{2\sqrt{3}}{3} \\[3ex] LHS \ne RHS \\[3ex] NO $ |
$
\underline{RHS} \\[3ex]
\csc\beta \\[3ex]
\beta = 120^\circ \\[3ex]
= \csc 120 \\[3ex]
= \dfrac{2\sqrt{3}}{3} \\[3ex]
YES \\[3ex]
$
$ \beta = 300^\circ \\[3ex] = \csc 300 \\[3ex] = -\dfrac{2\sqrt{3}}{3} \\[5ex] RHS \ne LHS \\[3ex] NO $ |
$
\underline{LHS} \\[3ex]
\cos(2\alpha) + 14\sin^2\alpha \\[3ex]
\alpha = 60^\circ \\[3ex]
2\alpha = 2 * 60 = 120 \\[3ex]
\cos2\alpha = \cos 120 = -\dfrac{1}{2} \\[5ex]
\sin^2\alpha = (\sin 60)^2 = \left(\dfrac{\sqrt{3}}{2}\right)^2 = \dfrac{(\sqrt{3})^2}{2^2} = \dfrac{3}{4} \\[5ex]
14\sin^2\alpha = 14\left(\dfrac{3}{4}\right) = 7\left(\dfrac{3}{2}\right) = \dfrac{21}{2} \\[5ex]
= -\dfrac{1}{2} + \dfrac{21}{2} \\[5ex]
= \dfrac{-1 + 21}{2} \\[5ex]
= \dfrac{20}{2} \\[5ex]
= 10 \\[3ex]
YES \\[3ex]
$
$ \alpha = 120^\circ \\[3ex] 2\alpha = 2 * 120 = 240 \\[3ex] \cos2\alpha = \cos 240 = -\dfrac{1}{2} \\[5ex] \sin^2\alpha = (\sin 120)^2 = \left(\dfrac{\sqrt{3}}{2}\right)^2 = \dfrac{(\sqrt{3})^2}{2^2} = \dfrac{3}{4} \\[5ex] 14\sin^2\alpha = 14\left(\dfrac{3}{4}\right) = 7\left(\dfrac{3}{2}\right) = \dfrac{21}{2} \\[5ex] = -\dfrac{1}{2} + \dfrac{21}{2} \\[5ex] = \dfrac{-1 + 21}{2} \\[5ex] = \dfrac{20}{2} \\[5ex] = 10 \\[3ex] YES \\[3ex] $ $ \alpha = 240^\circ \\[3ex] 2\alpha = 2 * 240 = 480 \\[3ex] \cos2\alpha = \cos 480 \\[3ex] coterminal\:\: \angle \:\:of\:\: 480 = 480 - 360 = 120 \\[3ex] \cos2\alpha = \cos 480 = \cos 120 = -\dfrac{1}{2} \\[5ex] \sin^2\alpha = (\sin 480)^2 = (\sin 120)^2 = \left(\dfrac{\sqrt{3}}{2}\right)^2 = \dfrac{(\sqrt{3})^2}{2^2} = \dfrac{3}{4} \\[5ex] 14\sin^2\alpha = 14\left(\dfrac{3}{4}\right) = 7\left(\dfrac{3}{2}\right) = \dfrac{21}{2} \\[5ex] = -\dfrac{1}{2} + \dfrac{21}{2} \\[5ex] = \dfrac{-1 + 21}{2} \\[5ex] = \dfrac{20}{2} \\[5ex] = 10 \\[3ex] YES \\[3ex] $ $ \alpha = 300^\circ \\[3ex] 2\alpha = 2 * 300 = 600 \\[3ex] \cos2\alpha = \cos 600 \\[3ex] coterminal\:\: \angle \:\:of\:\: 600 = 600 - 360 = 240 \\[3ex] \cos2\alpha = \cos 600 = \cos 240 = -\dfrac{1}{2} \\[5ex] \sin^2\alpha = (\sin 600)^2 = (\sin 240)^2 = \left(\dfrac{\sqrt{3}}{2}\right)^2 = \dfrac{(\sqrt{3})^2}{2^2} = \dfrac{3}{4} \\[5ex] 14\sin^2\alpha = 14\left(\dfrac{3}{4}\right) = 7\left(\dfrac{3}{2}\right) = \dfrac{21}{2} \\[5ex] = -\dfrac{1}{2} + \dfrac{21}{2} \\[5ex] = \dfrac{-1 + 21}{2} \\[5ex] = \dfrac{20}{2} \\[5ex] = 10 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 10 $ |
$
\underline{LHS} \\[3ex]
3\tan\alpha\sin\alpha - 3\tan\alpha \\[3ex]
\alpha = 0^\circ \\[5ex]
\tan\alpha = \tan 0 = 0 \\[3ex]
\sin\alpha = \sin 0 = 0 \\[3ex]
= 3 * 0 * 0 - 3 * 0 \\[3ex]
= 0 - 0 \\[3ex]
= 0 \\[3ex]
YES \\[3ex]
$
$ \alpha = 90^\circ \\[5ex] \tan\alpha = \tan 90 \:\:is\:\: undefined \\[3ex] STOP \\[3ex] NO \\[3ex] $ $ \alpha = 180^\circ \\[5ex] \tan\alpha = \tan 180 = 0 \\[3ex] \sin\alpha = \sin 180 = 0 \\[3ex] = 3 * 0 * 0 - 3 * 0 \\[3ex] = 0 - 0 \\[3ex] = 0 \\[3ex] YES $ |
$ \underline{RHS} \\[3ex] 0 $ |